2010
DOI: 10.1002/jso.21682
|View full text |Cite
|
Sign up to set email alerts
|

Safety and potential benefit of hyperthermic intraperitoneal chemotherapy (HIPEC) in peritoneal carcinomatosis from primary or recurrent ovarian cancer

Abstract: The results of our study indicate the feasibility and the potential benefit of a protocol including systemic chemotherapy, surgical cytoreduction and HIPEC in patients with peritoneal carcinomatosis from ovarian cancer. A phase III trial to compare this approach with conventional treatment is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 44 publications
(75 reference statements)
0
27
0
2
Order By: Relevance
“…Argenta et al 55 reported a grade III to IV morbidity of 30%, with the adverse events reported being 1 instance of grade III acute renal injury and 2 instances of grade IV thrombocytopenia and neutropenia. In comparison, Delotte et al 77 reported 20% of patients experiencing grade III to IV complications, whereas Roviello et al, 81 with a smaller cohort, reported only 12% of patients experiencing grade III to IV complications. Bakrin et al 76 reported grade III to IV complications in 30% of procedures performed for advanced or recurrent disease without further subgroup analysis.…”
Section: Morbiditymentioning
confidence: 93%
“…Argenta et al 55 reported a grade III to IV morbidity of 30%, with the adverse events reported being 1 instance of grade III acute renal injury and 2 instances of grade IV thrombocytopenia and neutropenia. In comparison, Delotte et al 77 reported 20% of patients experiencing grade III to IV complications, whereas Roviello et al, 81 with a smaller cohort, reported only 12% of patients experiencing grade III to IV complications. Bakrin et al 76 reported grade III to IV complications in 30% of procedures performed for advanced or recurrent disease without further subgroup analysis.…”
Section: Morbiditymentioning
confidence: 93%
“…The HIPEC chemotherapy used, temperature and duration was described in all 37 studies (eTable 2). The most commonly used HIPEC chemotherapy was cisplatin (CDDP) that was used either alone [26,42,49,50,55], or in combination with other agents such as doxorubicin [36,37,41,45,56], paclitaxel [40] or mitomycin-C [34,57] Figure 1). Only one study reached median overall survival for CRS with and without HIPEC (64.4 months and 46.4, respectively).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of these studies are single institution studies with a limited number of patients. [39][40][41][42][43][44][45][46] and a few are multi institutional studies [47][48][49]. Most of the studies report results of HIPEC for first line and second line therapy together.…”
Section: Hipec As First Line Therapy For Ovarian Cancermentioning
confidence: 99%